Implications of alcohol consumption on adherence to antiretroviral therapy: Perceptions of older people living with HIV in South-western Uganda. - Wamaani H,; Luwaga, Rachel; Peter , Ampiire; Lauben, Nduhura; Kebirungi J,; Norbert , Tayebwa; Biira, Edith; Nakidde, Gladys; Sheruramukama, Joshua; Maling, Samuel (Student's Journal of Health Research Africa, 2025)
Background Alcohol consumption is associated with reduced ART adherence, poor quality of life, and worse treatment outcomes among people living with HIV. Though ART adherence levels in the older population globally have been reported to be high, they may be affected by increased levels of alcohol consumption in this population in lower and middle-income countries. We explored the implications of alcohol consumption on adherence to antiretroviral therapy in older persons living with HIV in Southwestern Uganda. Methods An explanatory qualitative study design was employed among 38 purposively selected older persons living with HIV in 6 health facilities in Southwestern Uganda. A total of 6 focus group discussions were held and audio recorded at the selected Health Facilities. Data was transcribed, translated, coded, and categorized into themes. Thematic analysis was used to give meaning to the data collected. Results Participants' reports varied, with some finding alcohol beneficial in terms of providing nutrients, especially from the brands made locally. Others reported that alcohol increases sexual libido and relieves their stress. Many, however, reported that alcohol affects adherence to ART as it increases forgetfulness of the time specified for swallowing the drugs. Conclusion Older people perceived alcohol consumption as a hindrance to adherence. Negative perceptions, such as alcohol having nutrients or increasing sexual libido, present difficulties in reducing the consumption of alcohol, especially in older people living with HIV. Recommendation There is a need for the incorporation of counseling on the effects of alcohol in the care patients receive from HIV care facilities.